Exact small sample properties of the instrumental variable estimator: A view from a different angle - Halvor Mehlum (University of Oslo, Department of Economics, 2004)
I derive the exact small sample properties of the instrumental variables estimator using a trigonometric approach. The distribution for the estimation error is decomposed into a product of three components - each with an intuitive interpretation. This approach helps the discussion on what underlies the exact shape of the estimator's distribution and in particular the possibility of a bimodal distribution.
Keywords: C30; 330; Instrument; variable; estimator; Schätztheorie; Theorie